Reducing Fire Response Time in Medan City by Determining Hydrant Points Using ArcGis Software and Optimizing Routes Using the Djisktra Algorithm - Stepvani, Putri; Saragi , Yosefin; Budiman, Irwan (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
The development of an area will increase the risk of fire. Fire will not only cause physical, material loss, it can also cause casualties. In a span of 3 years, 46 major fire cases were recorded, not including unregistered fire cases. To be able to reduce the losses incurred, the fire fighters must be able to meet the fire response time of 15 minutes. To be able to meet this response time, a water source that can be used to douse the fire is needed as well as the fastest route to get to the destination point in the shortest possible time. The method used for laying the hydrant is the distribution method using Arc Gis software. The results obtained are that it takes 26 hydrant locations that are scattered in several central business areas and densely populated in the 3 sub-districts.